Nora goes off script - Monaghan, Annabel (G. P. Putnam's Sons, 2022)
"Evvie Drake Starts Over meets Beach Read in this heartwarming and hilarious novel about a divorced romance channel screenwriter whose script about her marriage's collapse just might help her reclaim her life and find love." --